2022
DOI: 10.3390/antibiotics11040514
|View full text |Cite
|
Sign up to set email alerts
|

Multicenter Study of Carbapenemase-Producing Enterobacterales in Havana, Cuba, 2016–2021

Abstract: Surveillance of carbapenem resistance is particularly important for Enterobacterales, mainly in countries with limited healthcare resources. We conducted a cross-sectional study to detect carbapenem-resistant Enterobacterales at 10 sentinel hospitals in Havana, Cuba for a six year-period (2016–2021) by the National Reference Laboratory for Health Care-Associated Infections in the Pedro Kourí Institute. A total of 152 isolates were collected with phenotypic production of metallo-β-lactamase. NDM-type carbapenem… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

3
4
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
5

Relationship

1
4

Authors

Journals

citations
Cited by 6 publications
(7 citation statements)
references
References 26 publications
3
4
0
Order By: Relevance
“…This is higher than prevalences previously reported from Pakistan such as 21.84% [ 50 ], 25.5% [ 51 ], 9.6% [ 52 ] and 6.5% [ 45 ]. However, our results are in agreement with the global reports that CRE prevalence is at alarming rates, such as 65.0% from the USA [ 53 ], 42.6% from Cuba [ 54 ] and 34.3% from China [ 55 ]. We observed that K. pneumoniae is the leading CRE pathogen, accounting for 33.8% of the total CR load, followed by E. coli (24.4%) and Pseudomonas spp.…”
Section: Discussionsupporting
confidence: 92%
See 1 more Smart Citation
“…This is higher than prevalences previously reported from Pakistan such as 21.84% [ 50 ], 25.5% [ 51 ], 9.6% [ 52 ] and 6.5% [ 45 ]. However, our results are in agreement with the global reports that CRE prevalence is at alarming rates, such as 65.0% from the USA [ 53 ], 42.6% from Cuba [ 54 ] and 34.3% from China [ 55 ]. We observed that K. pneumoniae is the leading CRE pathogen, accounting for 33.8% of the total CR load, followed by E. coli (24.4%) and Pseudomonas spp.…”
Section: Discussionsupporting
confidence: 92%
“…However, tracheal aspirate (25.0%), urine (24.26%), pus (25.53%), and surgical units (51.4%), ICU (65.3%), medical units (43.5%), pediatric wards (71.4%) were the previously reported causes of CRE infections in Pakistan [ 45 , 52 ]. Worldwide reports established that ICU-related colonization of CRE is higher, with results such as 86.15%, 35.5%, 31.0%, 24.0% and 12.3%, thus favoring the resistance selection process [ 54 , 83 , 84 , 85 , 86 ]. The Greek System for the Surveillance of Antimicrobial Resistance reported that CR increased from <1% in 2001 to 42% in medical wards and to 72% in ICUs among K. pneumoniae isolates [ 25 ].…”
Section: Discussionmentioning
confidence: 99%
“…The Gram-negative rod most commonly identified worldwide as CPE is K. pneumoniae [ 16 , 21 , 22 ], which was also confirmed in our study. Carbapenemase-producing K. pneumoniae strains present a significant clinical problem due to their increased capacity for patient colonization, epidemic potential, and high antibiotic resistance [ 23 ].…”
Section: Discussionsupporting
confidence: 87%
“…Compared with a previous study in Cuba (2010−12) which showed a low incidence of bla NDM (1 in 220 CRA isolates) ( Quiñones et al., 2015 ), in the present study bla NDM was prevalent among CRA (29%) mainly in Acb complex, and distributed also to other species A. bereziniae, A. haemolyticus, A. johnsonii and A. junii , and there was a relatively lower prevalence of bla OXA-23 -like gene. In Cuba, the NDM-type enzyme has been found to be dominant in carbapenem-resistant Enterobacterales (2016−21) ( Yu et al., 2022b ). These findings contrast with the distribution of carbapenemase types among Acinetobacter and Enterobacterales found in other Latin American countries ( García-Betancur et al., 2021 ; Yu et al., 2022a ) and suggest the regional spread of bla NDM over Gram-negative bacteria in Cuba.…”
Section: Resultsmentioning
confidence: 99%
“…In Cuba, the NDM-type enzyme has been found to be dominant in carbapenem-resistant Enterobacterales (2016−21) ( Yu et al., 2022b ). These findings contrast with the distribution of carbapenemase types among Acinetobacter and Enterobacterales found in other Latin American countries ( García-Betancur et al., 2021 ; Yu et al., 2022a ) and suggest the regional spread of bla NDM over Gram-negative bacteria in Cuba.…”
Section: Resultsmentioning
confidence: 99%